Study on the moment-rotation behavior of eccentric rectangular hollow section cross-type connections under out-of-plane bending moment and chord stress. (15th March 2020) - Zhao, Bida; Sun, Chao; Li, Hui
Highlights: A semi-rigid model is established to predict the out-of-plane moment-rotation behavior of ERHS X-connections. The intercept moment and initial stiffness are determined through using a yield line model and a three-beam model. The established semi-rigid model is verified via numerical and experimental results. Abstract: This paper studies the moment-rotation behavior of unstiffened eccentric rectangular hollow section (ERHS) cross-type connections under out-of-plane bending moment (OPBM) and chord stress. A finite element (FE) model is established and calibrated by experimental data. A parametric study on the out-of-plane moment-rotation behavior of the ERHS connections is conducted. Based on the results, a mathematical model (essentially a semi-rigid model) considering strength degradation and chord stress is established to describe the moment-rotation behavior of the ERHS connections with a brace-to-chord depth ratio less than 0.95. The yield line and three-beam models are used to formulate the two key parameters of the semi-rigid model, the intercept moment and the flexural initial stiffness. The established semi-rigid model is verified via numerical and experimental results. It is found that the failure mode of the ERHS connection is chord wall plasticization, and the numerical model can well simulate the failure mode and M o - ψ o curves of the specimen. Moreover, it is shown that the rigid joint assumption is applicable to the ERHS connection with a brace-to-chord depth ratio equal to 1.0 and a chord half depth-to-thickness ratio less than 15. The presented research can help advance the understanding of the behavior of ERHS connections under OPBM and the proposed equations will facilitate future applications.